Beach management tools - concepts, methodologies and case studies, - Azuz-Adeath, Isaac; Muñoz-Sevilla, Norma Patricia; Rivera Arriaga, Evelia; Silva-Íñiguez, Lidia; Arizpe-Covarrubias, Oscar; Cervantes-Rosas, Omar D.; García Morales, Gisela; Arreola-Lizárraga, José Alfredo; Martínez Ríos, Laura; Cortés-Ruíz, Alejandra; Ortega-Rubio, Alfredo (Springer, 2018)
This chapter discusses processes and structures of nearshore (marine) and costal governance by focusing on microscale (beach level) situations, inside the Mexican legal and regulatory context. The document compares the efficiency and effectivity of national initiatives, programs and actions with the local –and sometime temporal- measures emanated at beach, community or county level. The principal focus of this research is the lack of articulation and the existence of temporal gaps between managerial decisions related with governance, among national and local institutions and stakeholders, and its impacts towards beach sustainability. Looking at several study places (most of them urban touristic beaches) in the Pacific, Gulf of California and Gulf of Mexico littoral, the paper identify the best local governance (microscale governance) practices, and stablish routes of action toward their implementation at national level.
Microscale governance and temporal regulations in beach management
Keywords: Beach management; Governance; Microscale governance; Mexico; Sistemas